Study of serum zinc status in Bangladeshi women taking oral contraceptives (BIRDEM Medical Journal, 2019)
Background: Birth control pills alter women’s reproductive cycle and suppress various endocrine functions. Primary alterations of endocrine functions have secondary effects on other chemical and enzyme functions of the body. A general lowering of the body’s nutrient base occurs in women on hormonal contraception. The biochemical profile of oral contraceptive pill user women showed different changes in plasma total protein, albumin and various trace minerals like serum zinc, copper, magnesium etc. Trace minerals are necessary for endocrine function. This study was designed to evaluate serum zinc levels of women taking oral contraceptives.Methods: This cross-sectional study was conducted at Department of Biochemistry, Mymensingh Medical College Hospital from July 2013 to June 2014. A total of 150 subjects were included in this study; among them 50women were selected as control (Group I),who were neither taking oral contraceptives at the time of selection nor had taken it during prior one year period and 100 women were included as case (Group II), those were taking oral contraceptives. Again Group II was divided as Group IIA included 50 women who were taking oral contraceptives for 3 months duration or less and Group IIB included 50 women who were taking oral contraceptives for 4 months – 5years duration. Student’s unpaired‘t’ test was used to analyze the data between groups. For analytical purpose 95% confidence limit (p